Schaum's outlines : physics for engineering and science - Browne, Michael E. (Schaum's outline series, 2010)
Confused by physics? Problem solved. This classic Schaum's Outline is the ideal review for when your engineering course requires some physics. Schaum's Outlines: Physics for Engineering and Science provides a succinct review of physics topics such as motion, energy, fluids, waves, heat, and magnetic fields.